Dimensi Tasawuf dalam Ilmu Nahwu: Kajian Kitab Al-Futuhat al-Quddusiyyah fi Syarh al-Muqaddimah al-Jurumiyyah Karya Ibn ‘Ajibah - Isbah, Faliqul; Miftahul Ula (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
Sufism is a science that discusses the idea of ​​the mind or spirituality, while nahwu discusses how to communicate verbally well. These two aspects must be balanced and in line with humans. One of the figures who discuss this is Ibn 'Ajibah in his work entitled al-Futuhat al-Quddusiyyah. This article seeks to reveal the dimensions of Sufism from the symbolic meanings contained in the science of nahwu. The symbolic meaning contained in the nahwu rules in the book al-Futuhat al-Quddusiyyah from the perspective of Sufism is that in the teaching of nahwu according to Ibn 'Ajibah it has a meaning in relation to Sufism. nahwu which is an outward science actually also has an inner meaning, humans should understand these two things so that there is no inequality in life. The view of Sufism in this book is condensed into three stages, namely takhalli, tahalli and tajalli. Takhalli is a symbolic meaning of fiil (work) as something that is progressive, a hard effort to remove all obstacles that hinder to be able to achieve makrifat to Allah. Tahalli is the symbolic meaning of Jazm, meaning steadfast, patient and consistent in undergoing mujahadah and fighting obstacles. The meaning of tajalli arises from the i’rab rafa’ symbol which means the high degree to be achieved by those who already have nun al-ananiyah or ego as a sign of i’rab rafa’.